ANALISIS STRUKTURALISME PADA PUISI KONTEMPORER RUMAHKU YANG BIRU KARYA ARIFIN C. NOER - Nuraisyah Nuraisyah; Liza Septa Wilyanti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to analyze a contemporary poem entitled Rumahku yang Biru using a structuralism approach. This study uses a qualitative approach with the research method used in writing that is descriptive qualitative method. The object of this research is Arifin C. Noer's poem entitled Rumahku yang Biru. The results of this study indicate that the poem belongs to the type of contemporary poetry, this can be seen from the results of the study of the physical structure and inner structure that builds the poem. As a suggestion, this research can be investigated more deeply so that the results obtained are more accurate.